2023
DOI: 10.3390/ijms24043772
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation in Osteoporosis: Molecular Mechanisms Involved and the Relationship with microRNAs

Abstract: Osteoporosis is characterized by the alteration of bone homeostasis due to an imbalance between osteoclastic bone resorption and osteoblastic bone formation. Estrogen deficiency causes bone loss and postmenopausal osteoporosis, the pathogenesis of which also involves oxidative stress, inflammatory processes, and the dysregulation of the expression of microRNAs (miRNAs) that control gene expression at post-transcriptional levels. Oxidative stress, due to an increase in reactive oxygen species (ROS), proinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 191 publications
3
45
0
Order By: Relevance
“…This cascade of events further impedes osteoblast differentiation and bone remodeling through diverse pathways, hastening the progression of osteoporosis. [59] Conversely, estrogen orchestrates the regulation of osteoclast activity by binding to estrogen receptors, thereby attenuating bone loss. [60] In summary, the intricate interplay between estrogen, immune responses, lipid metabolism, and inflammatory processes sheds light on the multifaceted mechanisms influencing the risk of hyperuricemia, and these insights contribute to a comprehensive understanding of the observed gender disparities.…”
Section: Discussionmentioning
confidence: 99%
“…This cascade of events further impedes osteoblast differentiation and bone remodeling through diverse pathways, hastening the progression of osteoporosis. [59] Conversely, estrogen orchestrates the regulation of osteoclast activity by binding to estrogen receptors, thereby attenuating bone loss. [60] In summary, the intricate interplay between estrogen, immune responses, lipid metabolism, and inflammatory processes sheds light on the multifaceted mechanisms influencing the risk of hyperuricemia, and these insights contribute to a comprehensive understanding of the observed gender disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of osteoporosis is multifaceted and complex, encompassing a range of factors including aging, oxidative stress, and in ammation [9] [10]. These factors collectively impact the skeleton, resulting in decreased bone density and structural fragility, thereby increasing the risk of fractures [43] [44]. Consequently, lower levels of HRR could increase the risk of developing osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we utilized H 2 O 2 as a stimulus to construct an injury model in vitro , aiming to simulate the underlying to simulate the mechanism of osteoporosis induced by the OVX model . In recent years, there has been significant attention toward the correlation between oxidative stress and osteoporosis, as well as the underlying molecular mechanisms. However, current solutions for reducing oxidative stress in bone are inadequate. Studies have also shown that CIN can inhibit ROS in different cell types, and that it may maintain cellular balance by eliminating ROS. , Therefore, in this study, we aimed to demonstrate that CIN pretreatment could eliminate ROS and enhance BMSCs’ resistance to H 2 O 2 exposure.…”
Section: Discussionmentioning
confidence: 99%